Measuring Social Desirability in Collectivist Countries: A Psychometric Study in a Representative Sample From Kazakhstan - Nurumov, Kaidar; Hernández-Torrano, Daniel; Ait Si Mhamed, Ali; Ospanova, Ulzhan (Frontiers in Psychology, 2022)
Social desirability bias (SDB) is a pervasive measurement challenge in the social sciences and survey research. More clarity is needed to understand the performance of social desirability scales in diverse groups, contexts, and cultures. The present study aims to contribute to the international literature on social desirability measurement by examining the psychometric performance of a short version of the Marlowe-Crowne Social Desirability Scale (MCSDS) in a nationally representative sample of teachers in Kazakhstan. A total of 2,461 Kazakhstani teachers completed the MCSDS – Form C in their language of choice (i.e., Russian or Kazakh). The results failed to support the theoretical unidimensionality of the original scale. Instead, the results of Random Intercept Item Factor Analysis model suggest that the scale answers depend more on the method factor rather than the substantial factor that represents SDB. In addition, an alternative explanation indicates that the scale seems better suited to measuring two SDB correlated factors: attribution and denial. Internal consistency coefficients demonstrated unsatisfactory reliability scores for the two factors. The Kazakhstani version of the MCSDS – Form C was invariant across geographic location (i.e., urban vs. rural), language (i.e., Kazakh vs. Russian), and partially across age groups. However, no measurement invariance was demonstrated for gender. Despite these limitations, the analysis of the Kazakhstani version of the MCSDS – Form C presented in this study constitutes a first step in facilitating further research and measurement of SDB in post-Soviet Kazakhstan and other collectivist countries.